2023
DOI: 10.1159/000531824
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Hematologic Parameters in Young Patients with Retinal Vein Occlusion

Abstract: <b><i>Introduction:</i></b> The aim of this study was to investigate the characteristics of hematologic parameters in young patients with retinal vein occlusion (RVO). <b><i>Methods:</i></b> All participants underwent routine ocular examinations and blood sample tests. Hematologic parameters obtained from a complete blood count, as well as the calculation of specific inflammatory indices, were compared between young patients with RVO and the control subjects. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[21] NLR, one of the most studied inflammatory markers due to the close relationship between RVO and atherosclerosis, is high in patients with RVO in many studies, suggesting that it could be used as a predictive marker in identifying the risk of RVO. [8][9][10] Kazantzis et al [9] reported that NLR was superior to other inflammatory indicators in predicting the inflammatory status of RVO. In the current study, NLR has the highest AUC (0.817) according to ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[21] NLR, one of the most studied inflammatory markers due to the close relationship between RVO and atherosclerosis, is high in patients with RVO in many studies, suggesting that it could be used as a predictive marker in identifying the risk of RVO. [8][9][10] Kazantzis et al [9] reported that NLR was superior to other inflammatory indicators in predicting the inflammatory status of RVO. In the current study, NLR has the highest AUC (0.817) according to ROC analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] In another study, elevated SII was found to be correlated with high levels of IL-6 and VEGF in patients with RVO. [ 8 ] Zuo et al [ 10 ] found that the AUC of SII (0.666) was highest in patients with RVO. In their study, the optimal cutoff value of SII to predict RVO was > 326.46, with a sensitivity of 66.1% and specificity of 58.9%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations